Intraventricular SEEG and laser ablation for the treatment of infantile spasm: Technical note - Xinghua Xu; Qun Wang; Yining Zhao; Xin Xu; Zhichao Gan; Shiyu Zhang; Xiaolei Chen (Brain and Behavior, 2023)
Abstract Objectives Infantile spasm (IS) is an epileptic encephalopathy with ongoing neurological damage due to seizures and epileptiform abnormalities. Epilepsy surgery is considered for children refractory to drug therapy, especially when there is a focal brain lesion. In this study, we investigated the feasibility and efficacy of intraventricular stereotactic electroencephalography (SEEG) and laser ablation for the treatment of IS children with focal brain lesions. Methods We performed the first reported study using ventriculoscopic laser ablation to treat IS. Seven IS children with drug‐resistant epilepsy and definite encephalomalacia on brain magnetic resonance imaging scan were included in this study. Ablation was performed after confirmation of epileptiform discharges by SEEG under the surveillance of ventriculoscope. Results The median follow‐up time for the cohort was 3.1 years and 86% (6/7) of the children had an Engel class ≤III epilepsy at the final follow‐up. Five (71%) children had a reduction in seizure medication usage, and the other two were on the same amount as preablation. None of the children experienced serious new neurological deficits. Laser ablation might result in seizure freedom by destroying the local brain network and blocking the spread of abnormal discharges. Conclusions Intraventricular SEEG and laser ablation was feasible and effective for the treatment of IS. Further studies are warranted.